Dynamical susceptibilities of the Falicov-Kimball model with correlated hopping: general approach - Shvaika, A.M.; Farenyuk, O.Ya. (Condensed Matter Physics, 2009)
The Falicov-Kimball model with correlated hopping is studied in the limit of in nite spatial dimensions. Dynamical susceptibilities are calculated using the generalization of the Dynamical Mean-Field Theory (DMFT), which is based on expansion over electron hopping around the single-site limit. A special case of semi-elliptic density of states and diagonal correlated hopping is considered numerically and the absence of phase transition for all temperatures except T = 0 is demonstrated, which corresponds to the known results. Дослiджується модель Фалiкова-Кiмбала з корельованим переносом в границi безмежної розмiрностi простору. Динамiчнi сприйнятливостi розраховуються за допомогою теорiї динамiчного середнього поля, що ґрунтується на розвиненнях за електронним переносом навколо одновузлової границi. Дослiджується чисельно частковий випадок напiвелiптичної густини станiв та дiагонального корельованого переносу та показано вiдсутнiсть фазових переходiв для всiх температур крiм T = 0, що узгоджується з вiдомими результатами.